Strategi Pemanfaatan Media Sosial Instagram Sebagai Media Komunikasi Pemasaran - Rizky Firdaus, Adam; Shella Emawaty, Umi (Fakultas Ekonomi Universitas Gresik, 2023)
The Social media growth today seems inseparable in daily basis. Social media also needed for business actors. Along with the growth of local brands, all business actors rely on social media to introduce and promote their product. It is related to this research